Design and Control of a Linear Rotary Electro-Hydraulic Servo Drive Unit - Andrzej Milecki; Arkadiusz Jakubowski; Arkadiusz Kubacki (Applied Sciences, 2023)
In this paper, a new solution for an electro-hydraulic servo drive is proposed, which consists of two electro-hydraulic servo drives: one with a hydraulic cylinder and one with a hydraulic rotary motor. In the proposed drive, the linear actuator is attached to a horizontal base and the hydraulic motor is mounted on the actuator piston rod. Thus, the output signal of the drive is the lifting and lowering of the element suspended on the rope. The paper describes the structure, kinematics, dynamics, and control of a novel electro-hydraulic servo drive. A servo valve and a proportional valve are used to control the flow of the hydraulic cylinder and the hydraulic motor. Special attention is paid to the construction of two actuators in one drive unit. The controller is based on the PLC controller. The measuring system uses laser displacement sensors and an encoder. The results of laboratory investigations are discussed in the paper. The proposed drive contains all of the characteristics of a mechatronic device. The main contribution of this study is the proposal of the controller architecture and the algorithm to control the speed and position when lifting or lowering loads.